Pemertahanan Bahasa Gorontalo di Desa Kayu Kelor Kecamatan Ratolindo Kabupaten Tojo Una-Una - Tanio, Nur Fardani; Malabar, Sayama; Salam, Salam (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Language maintenance is a person’s effort to maintain and preserve their language when interacting with others. This study aims to describe the use of the language Gorontalo in society, the factors that influence the maintenance of the Gorontalo language, and strategies for maintaining the Gorontalo language carried out in Kayu Kelor village, Ratolindo subdistrict, Tojo Una-una Regency. The research uses qualitative decriptive research methods. The findddings indicate that (1) language use in the family domain predominantly follows the BG+BM, in the neighborhood domain, the BG+BM, in the employment domain the BM+BI, in the religious domain, the BM+BG. The preservatioan of the Gorontalo language influeced by family, social interactions, communication intesity, activies, and personal desire. The strategies preservation Gorontalo language using the Gorontalo language as a means of communication and intergrating language and culture.